2013
DOI: 10.1080/09658211.2012.704927
|View full text |Cite
|
Sign up to set email alerts
|

When does meaning making predict subjective well-being? Examining young and older adults in two cultures

Abstract: Two studies in different cultures (Study 1: USA, N=174, Study 2: Trinidad, N=167) examined whether meaning making, (i.e., both searching for meaning, and directing behaviour) is positively related to subjective well-being (SWB) by age (younger, older adults). In both studies, participants self-reported engagement in meaning making, and SWB (e.g., affect, future time perspective, psychological well-being). In Study 1, young Americans (compared to older) more frequently used their past to direct behaviour but do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 83 publications
3
29
1
1
Order By: Relevance
“…Thus, culture and life phase are co-varying. This co-variation might also be the reason why we did not replicate previous work showing that the directing-behaviour function is common in Trinidad (Alea & Bluck, 2013; Alea, in press). The current Trinidadian sample was older overall (and within each age group) compared with previous work, and younger age groups more often use the directive function (e.g., Bluck & Alea, 2009; Webster & McCall, 1999).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Thus, culture and life phase are co-varying. This co-variation might also be the reason why we did not replicate previous work showing that the directing-behaviour function is common in Trinidad (Alea & Bluck, 2013; Alea, in press). The current Trinidadian sample was older overall (and within each age group) compared with previous work, and younger age groups more often use the directive function (e.g., Bluck & Alea, 2009; Webster & McCall, 1999).…”
Section: Discussioncontrasting
confidence: 85%
“…A shorter time orientation has been found to predict less often using the past to direct behavior (Bluck & Alea, 2009), a memory function that seems salient in Trinidad. For example, Alea and Bluck (2013) using the directive function subscale of the Thinking About Life Experiences Scale (TALE, Bluck & Alea, 2011) found, that Trinidadian adults (Study 2) use the past to direct behavior more than Americans (Study 1). However, no direct statistical comparisons were made between the two cultures.…”
Section: Cultural Contexts: Being American and Being Trinidadianmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that meaning making is associated with positive psychological adjustment, well-being and maturity (see McKay et al, in press;Singer, Blagov, Berry, & Oost, 2013). The relationship between meaning and well-being, however, is complex and is influenced by individual characteristics such as age (e.g., Alea & Bluck, 2013;McLean, Breen, & Fournier, 2010), culture (Alea & Bluck, 2013) and personality (Lilgendahl, McLean, & Mansfield, 2013); the type of memory (Lilgendahl et al, 2013); and the aspect of meaning, such as sophistication (McLean et al, 2010) or number (McLean et al, 2010) and valence (Banks & Salmon, 2013;Lilgendahl & McAdams, 2011) of self-event connections (statements about how the event connects to a stable or changed aspect of the self). Thorne and McLean (2001) argue that the content of an SDM is the main theme emphasised in it and reflects one of the individual's primary concerns.…”
Section: Studymentioning
confidence: 97%
“…More generally, adolescence and young adulthood involve identity formation; indeed, this sort of meaning-making may explain why people preferentially remember events from these ages (10-30 years old), producing a reminiscence bump (Fitzgerald, 1996; see Koppel & Rubin, 2016, for discussion of multiple bumps). Alea and Bluck (2013) also found that older Trinidadians use autobiographical memories to make meaning less than young Trinidadians. This pattern only partially replicated in an American sample, but it raises the possibility that older adults search for meaning, and thus engage in magical thinking, less frequently than young adults do.…”
mentioning
confidence: 91%